INTERPERSONAL COMMUNICATION: FROM THE HISTORY OF IDEAS - N. V. Kazarinova (Дискурс)
The article is devoted to the theory of «Coordinated Management of Meaning» that problematizes aspects of interpersonal communication that have not been the subject of theoretical interest in other concepts.